The Online Seminar on the Effects of Metabolic Syndrome on Covid-19 Patients among Urban Communities - Fonny Cokro; Nathacia Nathacia; Meilani Eka Putri; Genoveva Della; Felicia Christian (Institute for Research and Community Services, 2022)
Metabolic syndrome is typically characterized by hypertension, diabetes mellitus, dyslipidemia, and obesity—all of which can contribute to a higher risk of acute coronary syndrome (ACS). Mounting evidence also shows how metabolic syndrome may lead to worsening symptoms in covid-19 patients, thus resulting in more fatal cases. Therefore, what is urgently needed is the efforts to improve public awareness of the adverse effects of metabolic syndrome on covid-19 patients and the importance of health protocols against covid-19 transmission. An online seminar via zoom was held to support the fight against the covid-19 pandemic among the urban communities, which were chosen due to the prevalence of metabolic syndrome in these communities. The two-hour online counseling was also held to commemorate World Pharmacist Day, which fell on September 26, 2020. The responses to the questionnaire revealed that the majority of participants had a better understanding of the metabolic syndrome, its risks, its detrimental influence on the conditions of covid-19 patients, and the efforts to prevent Covid-19 transmissions. The seminar is expected to contribute to the government’s efforts to bolster the community’s awareness of the importance of health protocols